2015
DOI: 10.1080/14763141.2015.1084031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of basketball shoe mass, outsole traction, and forefoot bending stiffness on three athletic movements

Abstract: Prior research has shown that footwear can enhance athletic performance. However, public information is not available on what basketball shoe properties should be selected to maximise movement performance. Therefore, the purpose of the study was to investigate the influence of basketball shoe mass, outsole traction, and forefoot bending stiffness on sprinting, jumping, and cutting performance. Each of these three basketball shoe properties was systematically varied by ± 20% to produce three shoe conditions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 24 publications
3
44
1
1
Order By: Relevance
“…Worobets and Wannop (2015) showed similar results in a study on a group of 20 basketball players. They found performance increases of 1.7% in a timed cutting drill when bending stiffness was increased by 50% (0.22 to 0.33 Nm/deg).…”
Section: Multidirectional and Lateral Movementssupporting
confidence: 77%
See 1 more Smart Citation
“…Worobets and Wannop (2015) showed similar results in a study on a group of 20 basketball players. They found performance increases of 1.7% in a timed cutting drill when bending stiffness was increased by 50% (0.22 to 0.33 Nm/deg).…”
Section: Multidirectional and Lateral Movementssupporting
confidence: 77%
“…A major limitation in terms of establishing a standard testing method is the fact that access to testing equipment or funds to purchase testing equipment may not be universally accessible. Potential solutions to this issue may include a testing method that requires limited mechanical equipment or data acquisition hardware, such as the method used by Worobets and Wannop (2015) or the introduction of a control or sample shoe that is readily available and could be tested alongside all experimental test footwear, establishing a relationship between the various test methods and setups.…”
Section: Multidirectional and Lateral Movementsmentioning
confidence: 99%
“…increments is a limitation of this study [22]. However, we specifically chose to use the Vertec to measure vertical jump height instead of a device with greater validity such as a force platform so that we could directly compare the results of this study with previous research that examined the effects of footwear bending stiffness on vertical jump height performance [8,9,23]. The results of this study are similar to those found by previous research which demonstrated that increasing the stiffness of shoes (via the use of a carbon fiber plate inserted into the shoe midsole, with a bending stiffness approximately five times greater than the control condition) resulted in a 1.7 cm increase in vertical jump height for a group of 25 male participants [8].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that increasing the stiffness of shoes (via the use of carbon fiber plates inserted into the shoe midsole) resulted in a 1.7 cm increase in vertical jump height for a group of 25 participants [8]. However, systematically increasing footwear stiffness was not found to have an effect on jump height in 20 recreational basketball players [9]. Sprint running performance in 34 high-level sprinters was improved by the use of carbon fiber plates inserted under the shoe sock liner in track spikes to increase forefoot bending stiffness [10].…”
Section: Introduction mentioning
confidence: 92%
“…RICYDE. Revista internacional de ciencias del deporte, 49(13),[273][274][275][276][277][278][279][280][281][282][283][284] …”
Section: Introductionunclassified